An ultrathin laser photovoltaic cell and a preparation method thereof
Patent Information
- Application Number
- CN202310718235.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-06-16
AI Technical Summary
[0003]传统结构的红外激光光伏电池为了充分吸收激光,通常要求吸收层厚度很厚,一般在几个微米甚至十几个微米量级,远大于工作波长,这不但使得器件的制备成本较高,而且限制了器件的电学性能
[0021] 1. By selecting a suitable material system and adjusting the component parameters, a device design scheme with universal applicability within a certain range can be obtained;
Smart Images

Figure CN116632096B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of laser photovoltaic cell technology, and specifically relates to an ultrathin laser photovoltaic cell and its fabrication method, particularly to a laser photovoltaic cell with an asymmetric subwavelength Fabry-Pérot (FP) resonant cavity structure and its fabrication method. Background Technology
[0002] Laser energy conversion systems are a new type of energy transmission system, commonly used in wireless and fiber optic energy transmission. Photovoltaic cells receive high-energy laser light and convert it into electrical energy, initially primarily used for space energy transmission, such as powering space stations and satellites. With increasing civilian demand, laser energy converters are also being used in long-distance wireless power supply for unmanned aerial vehicles and sensors, as well as in fiber optic energy transmission. Fiber optic energy transmission is currently the most promising application area for laser energy converters. Fiber optic power transmission systems possess excellent resistance to electromagnetic interference and environmental stability, playing a crucial role in areas inaccessible by power grids, such as polar regions, the seabed, ammunition depots, mines, and oil fields. A fiber optic power transmission system mainly consists of three parts: a laser source, optical fiber, and a laser energy converter (i.e., a laser photovoltaic cell). Therefore, the laser photovoltaic cell is one of the core components of a fiber optic power transmission system.
[0003] Traditional infrared laser photovoltaic cells typically require a very thick absorption layer, usually on the order of several micrometers or even tens of micrometers, to fully absorb laser light. This thickness is much greater than the operating wavelength, which not only increases the fabrication cost of the device but also limits its electrical performance. Overcoming these difficulties requires making the absorption layer as thin as possible; however, reducing the thickness reduces laser absorption, thereby lowering the quantum efficiency and the final photoelectric conversion efficiency. Therefore, designing a laser photovoltaic cell that can fully absorb incident light while possessing an ultrathin subwavelength thickness has significant practical application value. This invention discloses a subwavelength ultrathin laser photovoltaic cell based on an asymmetric subwavelength Fabry-Perot resonator structure. This structure has a certain degree of universality and can be optimized for different wavelengths to meet the application requirements of lasers of different wavelengths. Summary of the Invention
[0004] The present invention aims to provide an ultrathin laser photovoltaic cell with stable performance, long service life and certain universality, and its preparation method.
[0005] The ultrathin laser photovoltaic cell provided by this invention uses Au / InP / In 1-x Ga x As y P 1-yThe InP / In asymmetric FP cavity structure, through careful design, not only has a device structure thickness much smaller than the operating wavelength, exhibiting subwavelength characteristics, but also achieves near 100% absorption of incident light based on strong interference effects. 1-x Ga x As y P 1-y It is a set of lattice-matched, tunable bandgap material systems. By adjusting the values of x and y, it is possible to maintain In 1-x Ga x As y P 1-y By matching the lattice constant with InP, absorption region materials with different band gaps can be obtained, thus matching lasers of different wavelengths.
[0006] Specifically, the structure of the ultrathin laser photovoltaic cell provided by this invention is shown in [reference needed]. Figure 1 As shown, it includes a metal reflective layer 1, a back field layer 2, a base layer 3, an emission layer 4, a front field layer 5, and an electrode contact layer 6 stacked sequentially; the base layer and the emission layer are combined to form a superabsorption layer structure; the material composition parameters of the superabsorption layer are changed to achieve energy conversion for lasers of different wavelengths, and the thickness of the superabsorption layer is changed to achieve superabsorption at the working wavelength; wherein:
[0007] The metal reflective layer 1 is a gold thin film prepared by electron beam evaporation with a thickness of 50-200 nm;
[0008] The back field layer 2 is a heavily doped P-type InP layer used to block the diffusion of electrons to the interface, with a thickness of 50-300 nm.
[0009] The base layer 3 and emitter layer 4 are respectively lightly doped P-type In1-xGaxAsyP1-y and heavily doped N-type In. 1-x Ga x As y P 1-y They are integrated into a superabsorption layer. The material composition is determined according to the working wavelength, and the thickness of the superabsorption layer is determined according to the superabsorption conditions, with a thickness range of 10-800 nm.
[0010] The front field layer 5, also called the window layer in solar cells, is a heavily doped N-type InP layer used to block the diffusion of holes to the interface and passivate the surface of the emitter layer 4. Its thickness is 50-300 nm.
[0011] The electrode contact layer 6 is a heavily doped N-type In. 1-x Ga x As y P 1-y It is used for ohmic contact of the top electrode, while preventing penetration into the absorption layer during the electrode alloying and annealing processes.
[0012] In this invention, the superabsorbent layer structure is an asymmetric FP cavity structure of metal / non-absorbing medium / medium / non-absorbing medium. Through careful design, its structural thickness is much smaller than the operating wavelength, and based on the strong interference effect, it can achieve nearly 100% absorption of incident light. Specifically, the battery uses Au / InP / In... 1-x Ga x As y P 1-y / InP structure, by adjusting the medium In 1-x Ga x As y P 1-y The composition of the medium In can be adjusted to change its bandgap, thereby achieving absorption of lasers of different wavelengths; by adjusting the In medium 1-x Ga x As y P 1-y The thickness is adjusted to achieve superabsorption conditions, thus realizing near 100% superabsorption of the working wavelength laser. Specifically, In 0.53 Ga 0.47 As has the same lattice constant as InP, and In based on an InP substrate, the lattice constant of In is consistent with that of the substrate. 1-x Ga x As y P 1-y It can be regarded as InP and In 0.53 Ga 0.47 As is composed of elements in a certain proportion; changing the values of x and y can make In... 1-x Ga x As y P 1-y The bandgap is continuously distributed between 0.74 eV and 1.35 eV, therefore the ranges of x and y are 0 ≤ x ≤ 0.47 and 0 ≤ y ≤ 1, respectively. Medium In 1- x Ga x As y P 1-y The thickness is 10-800nm to ensure that the absorption layer thickness is within the subwavelength range of the working wavelength.
[0013] In this invention, the overall thickness of the device is within the subwavelength range.
[0014] In this invention, the material of the back reflective layer (1) can be selected from metals such as silver, aluminum, platinum, and copper, depending on the absorption characteristics of the selected material in the working wavelength band. Gold is preferred.
[0015] In this invention, the back field layer 2 is made of p-type heavily doped InP, and the base layer 3 and emitter layer 4 are respectively made of p-type lightly doped InP. 1-x Ga x Asy P 1-y and N-type heavily doped In 1-x Ga x As y P 1-y The composition is adjusted according to the operating wavelength. The front field layer 5 is N-type heavily doped InP, and the electrode contact layer 6 is N-type heavily doped In. 1-x Ga x As y P 1-y The above materials can be grown using MOCVD or MBE methods.
[0016] This invention also provides a method for preparing the above-mentioned ultrathin laser photovoltaic cell, the specific steps of which are as follows:
[0017] (1) Optical design of ultrathin laser photovoltaic cell devices: for InP / In 1-x Ga x As y P 1-y By selecting values for x and y in the material system, an InP / In lattice matching with InP is obtained. 1-x Ga x As y P 1-y Materials, including bandgap width, matching wavelength, and laser photon energy; after determining the optical parameters of the corresponding materials, for Au / InP / In 1-x Ga x As y P 1-y Optical optimization calculations were performed on the InP device structure to obtain InP that satisfies the superabsorption condition. 1-x Ga x As y P 1-y The thickness of the absorption layer;
[0018] (2) Electrical Design of Ultrathin Laser Photovoltaic Cell Devices: Obtaining In that satisfies the superabsorption condition 1-x Ga x As y P 1-y After determining the thickness of the absorption layer, the electrical structure of this optical structure is designed. The absorption layer is decomposed into a heavily doped N-type emitter layer and a lightly doped P-type absorber layer, with the total thickness equal to the thickness of the absorption layer under superabsorption conditions. The two InP layers correspond to the heavily doped P-type InP back field layer and the heavily doped N-type InP front field layer, respectively. The contacts are set as ideal ohmic contacts. After determining the electrical parameters of each layer, such as thickness, mobility, bandgap, doping concentration, and electron affinity, the device is electrically simulated to calculate the photoelectric conversion efficiency and obtain the optimal device structure.
[0019] (3) Fabrication of ultrathin laser photovoltaic cell devices: After obtaining suitable device parameters through optical and electrical design, actual fabrication is carried out based on the optimized device parameters; an InGaAs sacrificial layer, a heavily p-doped InP back field layer, and a lightly p-doped InP back field layer are sequentially grown on an InP single crystal substrate. 1-x Ga x As y P 1-y Absorber layer, N-type heavily doped In 1-x Ga x As y P 1-y Emitter layer, N-type heavily doped InP front field layer, N-type heavily doped In 1-x Ga x As y P 1-y Electrode layer; after depositing a strip-shaped top electrode on the electrode layer, the excess electrode layer is etched away with a mixture of H3PO4 / H2O2 to protect the device area. Then, the excess InP front field layer and two In layers are etched away sequentially with a mixture of concentrated hydrochloric acid and H3PO4 / H2O2. 1-x Ga x As y P 1-y The bottom electrode is deposited on the outer region of the device on the InP back field layer, and after annealing, the desired cell structure is obtained. The front side of the device is protected with photoresist and adhered to a quartz substrate with paraffin wax. The back InP substrate and InGaAs sacrificial layer are removed sequentially with hydrochloric acid and a mixture of H3PO4 / H2O2. Au is deposited on the back side of the InP back field layer using electron beam evaporation and adhered to a quartz or silicon substrate with an adhesive. The paraffin wax and photoresist on the front side are removed with carbon tetrachloride and acetone to obtain an Au / InP / In... 1-x Ga x As y P 1-y / InP structure battery devices.
[0020] Compared with the prior art, the advantages of the present invention are as follows:
[0021] 1. By selecting a suitable material system and adjusting the component parameters, a device design scheme with universal applicability within a certain range can be obtained;
[0022] 2. Using an asymmetric FP cavity structure, a laser photovoltaic cell with an ultrathin absorption layer is obtained, which can achieve super absorption within the working wavelength, enabling the device to obtain electrical performance superior to traditional devices without losing light absorption.
[0023] 3. Optimize device parameters through simulation to guide the structural and process design of devices and reduce trial and error costs.
[0024] This laser photovoltaic cell can serve as a power source for downstream monitoring, sensors, lighting equipment, and other instruments, demonstrating broad applications and promising development prospects in fields such as ammunition depots, mines, and the seabed. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the ultrathin laser photovoltaic cell structure of the present invention.
[0026] Figure 2 For In corresponding to a wavelength of 1064nm 0.81 Ga 0.19 As 0.42 P 0.58 The relationship between the absorptivity of ultrathin laser photovoltaic cells and the thickness of the absorption layer.
[0027] Figure 3 For In corresponding to a wavelength of 1310nm 0.68 Ga 0.32 As 0.69 P 0.31 The relationship between the absorptivity of ultrathin laser photovoltaic cells and the thickness of the absorption layer.
[0028] Figure 4 For In corresponding to a wavelength of 1550nm 0.53 Ga 0.47 The relationship between the absorption rate of ultrathin laser photovoltaic cells and the thickness of the absorption layer.
[0029] Figure 5 For In with different absorption layer thicknesses corresponding to 1550nm 0.53 Ga 0.47 JV curve of ultrathin laser photovoltaic cell. Detailed Implementation
[0030] The preferred embodiments of the present invention are given below to enable a better understanding of the process of the present invention.
[0031] This invention uses lasers with wavelengths of 1064nm, 1310nm, and 1550nm as examples to provide corresponding design and fabrication methods for laser photovoltaic cells. By rationally optimizing device parameters, highly efficient ultrathin laser photovoltaic cells are obtained. The specific steps are as follows:
[0032] (1) Device optical design: For InP / In 1-x Ga x As y P 1-y For the material system, taking x as 0.19 and y as 0.42, In lattice-matched InP can be obtained. 0.81 Ga 0.19 As 0.42 P 0.58The material has a bandgap of 1.06 eV, matching the 1.17 eV photon energy of a 1064 nm wavelength laser; by setting x to 0.32 and y to 0.69, an In lattice-matched InP material can be obtained. 0.68 Ga 0.32 As 0.69 P 0.31 The material has a bandgap of 0.91 eV, matching the 0.95 eV photon energy of a 1310 nm wavelength laser; by setting x to 0.47 and y to 1, an In lattice-matched InP can be obtained. 0.53 Ga 47 As material has a bandgap of 0.74 eV, matching the 0.8 eV photon energy of a 1550 nm wavelength laser. After determining the optical parameters of the corresponding material, the Au / InP / In... 1-x Ga x As y P 1-y Optical optimization calculations were performed on the InP device structure to obtain InP that satisfies the superabsorption condition. 1-x Ga x As y P 1-y The thickness of the absorption layer;
[0033] (2) Device electrical design: In obtaining In that satisfies the superabsorption condition 1-x Ga x As y P 1-y After determining the thickness of the absorption layer, the electrical structure can be designed for this optical structure. The absorption layer is decomposed into a heavily doped N-type emitter layer and a lightly doped P-type absorber layer, with the total thickness equal to the thickness of the absorption layer under superabsorption conditions. The two InP layers correspond to the heavily doped P-type InP back field layer and the heavily doped N-type InP front field layer, respectively. The contacts are set as ideal ohmic contacts. After determining the electrical parameters of each layer, such as thickness, mobility, bandgap, doping concentration, and electron affinity, the device can be electrically simulated to calculate the photoelectric conversion efficiency and obtain the optimal device structure.
[0034] (3) Device fabrication method: After obtaining suitable device parameters through optical and electrical design, actual fabrication is carried out based on the optimized device parameters. An InGaAs sacrificial layer, a heavily p-doped InP back field layer, and a lightly p-doped InP back field layer are sequentially grown on an InP single-crystal substrate. 1-x Ga x As y P 1-y Absorber layer, N-type heavily doped In 1-x Ga x As y P 1-y Emitter layer, N-type heavily doped InP front field layer, N-type heavily doped In0.53 Ga 0.47 As the electrode layer. After depositing a strip-shaped top electrode on the electrode layer, the excess electrode layer is etched away with a mixture of H3PO4 / H2O2 to protect the device area. Then, the excess InP front field layer and two InP layers are etched away sequentially with concentrated hydrochloric acid and a mixture of H3PO4 / H2O2. 1-x Ga x As y P 1-y The bottom electrode is deposited on the outer region of the device on the InP back field layer, and after annealing, the desired cell structure is obtained. The front side of the device is protected with photoresist and adhered to a quartz substrate with paraffin wax. The back InP substrate and InGaAs sacrificial layer are removed sequentially with hydrochloric acid and a mixture of H3PO4 / H2O2. Au is deposited on the back side of the InP back field layer using electron beam evaporation and adhered to a quartz or silicon substrate with an adhesive. The paraffin wax and photoresist on the front side are removed with carbon tetrachloride and acetone to obtain an Au / InP / In... 1-x Ga x As y P 1-y / InP structure battery devices.
[0035] Furthermore:
[0036] (1) Optical Design: Numerical Calculation of Au / InP / In under Laser Irradiation at Wavelengths of 1064nm, 1310nm, and 1550nm 0.81 Ga 0.19 As 0.42 P 0.58 / InP、Au / InP / In 0.68 Ga 0.32 As 0.69 P 0.31 / InP、Au / InP / In 0.53 Ga 0.47 The absorption rates of the three asymmetric FP cavity structures AsP / InP at different absorption layer thicknesses are calculated. Considering the actual process requirements, the thickness of Au is taken as 200nm, the thickness of the two InP layers is 100nm, and the absorption layer thickness is taken as 10nm to 800nm. The change of the structure with the absorption layer thickness is calculated and the thickness of the absorption region corresponding to superabsorption is determined.
[0037] (2) Electrical simulation: Based on the thickness of several absorption regions corresponding to superabsorption and the relevant electrical parameters of each layer of material, 100mW / cm² was calculated using the finite element method. 2 The current density-voltage relationship of the device under laser irradiation at the corresponding wavelength is determined, and the open-circuit voltage, short-circuit current, fill factor and photoelectric conversion efficiency of the device are calculated accordingly to select an appropriate absorption region thickness.
[0038] The corresponding device structures are as follows:
[0039] See Figure 1 As shown, the device has a N-on-P type structure. The P-type absorption layer is lightly doped and relatively thick, while the N-type layer is heavily doped and relatively thin. The front field InP is heavily N-type doped, and the back field InP is heavily P-type doped, both with a thickness of 100 nm. The Au reflective layer is 200 nm thick. The electrode contact layer is heavily N-type doped with a thickness of 300 nm. It has the same shape as the top electrode and does not block the laser. The area of the top electrode does not exceed 5% of the total device area. The bottom electrode is a cubic electrode deposited on the InP back field layer, and the electrode thickness is 200 nm.
[0040] Figure 2 Au / InP / In corresponding to a 1064nm wavelength laser 0.81 Ga 0.19 As 0.42 P 0.58 The curve shows the relationship between the absorption rate of the / InP structure and the thickness of the absorption layer. It can be seen that there are six peak absorption points in the thickness range of 10 nm to 800 nm, which correspond to the first to sixth order superabsorption modes of this structure. Among them, the absorption rate of the device corresponding to the third (fourth) order superabsorption exceeds 95% (99%), and the corresponding device absorption layer thickness is 325 (478) nm.
[0041] Figure 3 Au / InP / In corresponding to a 1310nm wavelength laser 0.68 Ga 0.32 As 0.69 P 0.31 The curve shows the relationship between the absorptivity of the / InP structure and the thickness of the absorption layer. It can be seen that there are four peak absorption points in the thickness range of 10 nm to 800 nm, which correspond to the first to fourth order superabsorption modes of this structure. Among them, the absorptivity of the device corresponding to the third (fourth) order superabsorption exceeds 90% (97%), and the corresponding device absorption layer thickness is 450 (637) nm.
[0042] Figure 4 Au / InP / In corresponding to a 1550nm wavelength laser 0.53 Ga 0.47 The absorption rate of the As / InP structure varies with the thickness of the absorption layer. It can be seen that four peak absorption points appear in the thickness range of 10 nm to 800 nm, which correspond to the first to fourth order superabsorption modes of this structure. Among them, the absorption rate of the device corresponding to the third (fourth) order superabsorption exceeds 94% (99%), and the corresponding device absorption layer thickness is 560 (780) nm.
[0043] Figure 5 Au / InP / In corresponding to a 1550nm wavelength laser 0.53 Ga 0.47The table shows the electrical performance of devices corresponding to the three higher-order superabsorption modes of the As / InP structure, and the electrical performance of devices with traditional thicker layers. The table also includes relevant battery performance parameters. Devices with superabsorption modes exhibit higher open-circuit voltage, fill factor, and energy conversion efficiency than traditional thicker devices. The energy conversion efficiency of traditional thicker devices is 36.8%, lower than the 42.2% and 41.3% for absorption layer thicknesses of 560nm and 780nm, respectively. The energy conversion efficiency at a 560nm absorption layer thickness is slightly lower than that at 780nm, but the thinner layer offers better commercial value.
Claims
1. An ultrathin laser photovoltaic cell, characterized in that, Using Au / InP / In 1-x Ga x As y P 1-y The InP / In asymmetric FP cavity structure, through design, allows the device structure thickness to be much smaller than the operating wavelength, exhibiting subwavelength characteristics. Furthermore, based on strong interference effects, the device absorbs nearly 100% of the incident light. 1-x Ga x As y P 1-y It is a set of lattice-matched, adjustable bandgap material systems. By adjusting the values of x and y, while maintaining In... 1-x Ga x As y P 1-y Absorption region materials with different bandgap widths are obtained when the lattice constant is matched with InP, thereby matching lasers of different wavelengths; specifically, it includes a metal reflective layer (1), a back field layer (2), a base layer (3), an emission layer (4), a front field layer (5), and an electrode contact layer (6) stacked sequentially; the base layer and the emission layer are combined to form a superabsorption layer structure; the material composition parameters of the superabsorption layer are changed to achieve energy conversion for lasers of different wavelengths, and the thickness of the superabsorption layer is changed to achieve superabsorption at the working wavelength; wherein: The metal reflective layer (1) is a gold thin film prepared by electron beam evaporation with a thickness of 50-200 nm; The back field layer (2) is a heavily doped P-type InP layer used to block the diffusion of electrons to the interface, with a thickness of 50-300 nm. The base layer (3) and emitter layer (4) are respectively lightly doped P-type In 1-x Ga x As y P 1-y and N-type heavily doped In 1- x Ga x As y P 1-y They are integrated into a superabsorption layer. The material composition is determined according to the working wavelength, and the thickness of the superabsorption layer is determined according to the superabsorption conditions, with a thickness range of 10-800 nm. The front field layer (5), also called the window layer in solar cells, is a heavily doped N-type InP, used to block the diffusion of holes to the interface and passivate the surface of the emitter layer (4), with a thickness of 50-300 nm. The electrode contact layer (6) is a heavily doped N-type In. 1-x Ga x As y P 1-y It is used for ohmic contact of the top electrode, while preventing penetration into the absorption layer during the electrode alloying and annealing processes.
2. The ultrathin laser photovoltaic cell according to claim 1, characterized in that, The superabsorbent layer structure is an asymmetric FP cavity structure of metal / non-absorbing medium / medium / non-absorbing medium; specifically, it adopts Au / InP / In 1-x Ga x As y P 1-y / InP structure, by adjusting the medium In 1-x Ga x As y P 1-y The composition of the medium In can be adjusted to change its bandgap, thereby achieving absorption of lasers of different wavelengths; by adjusting the In medium 1-x Ga x As y P 1-y The thickness is used to achieve the superabsorption condition, so as to achieve nearly 100% superabsorption of the working wavelength laser.
3. The laser photovoltaic cell according to claim 2, characterized in that, Medium In 1-x Ga x As y P 1-y In the medium In, the range of x and y is 0 ≤ x ≤ 0.47, 0 ≤ y ≤ 1. 1-x Ga x As y P 1-y The thickness ranges from 10 nm to 800 nm; the overall thickness of the device is in the subwavelength range.
4. The laser photovoltaic cell according to claim 1, characterized in that, The material of the back reflective layer (1) is silver, aluminum, platinum or copper.
5. A method for preparing an ultrathin laser photovoltaic cell as described in any one of claims 1-4, characterized in that, The specific steps are as follows: (1) Optical design of ultrathin laser photovoltaic cell devices: for InP / In 1-x Ga x As y P 1-y By selecting values for x and y in the material system, an InP / In lattice matching with InP is obtained. 1-x Ga x As y P 1-y Materials, including bandgap width, matching wavelength, and laser photon energy; after determining the optical parameters of the corresponding materials, for Au / InP / In 1-x Ga x As y P 1-y Optical optimization calculations were performed on the InP device structure to obtain InP that satisfies the superabsorption condition. 1-x Ga x As y P 1-y The thickness of the absorption layer; (2) Electrical Design of Ultrathin Laser Photovoltaic Cell Devices: Obtaining In that satisfies the superabsorption condition 1-x Ga x As y P 1-y After determining the thickness of the absorption layer, the electrical structure of this optical structure is designed. The absorption layer is decomposed into a heavily doped N-type emitter layer and a lightly doped P-type absorber layer, with the total thickness equal to the thickness of the absorption layer under superabsorption conditions. The two InP layers correspond to the heavily doped P-type InP back field layer and the heavily doped N-type InP front field layer, respectively. The contacts are set as ideal ohmic contacts. After determining the thickness, mobility, bandgap, doping concentration, electron affinity, and other electrical parameters of each layer of the device, the device is electrically simulated to calculate the photoelectric conversion efficiency and obtain the optimal device structure. (3) Fabrication of ultrathin laser photovoltaic cell devices: After obtaining suitable device parameters through optical and electrical design, actual fabrication is carried out based on the optimized device parameters; an InGaAs sacrificial layer, a heavily p-doped InP back field layer, and a lightly p-doped InP back field layer are sequentially grown on an InP single crystal substrate. 1-x Ga x As y P 1-y Absorber layer, N-type heavily doped In 1-x Ga x As y P 1-y Emitter layer, N-type heavily doped InP front field layer, N-type heavily doped In 1-x Ga x As y P 1-y Electrode layer; after depositing a strip-shaped top electrode on the electrode layer, the excess electrode layer is etched away with a mixture of H3PO4 / H2O2 to protect the device area. Then, the excess InP front field layer and two In layers are etched away sequentially with a mixture of concentrated hydrochloric acid and H3PO4 / H2O2. 1-x Ga x As y P 1-y In the first layer, a bottom electrode is deposited on the outer region of the device on the InP back field layer, and after annealing, the desired cell structure is obtained. The front side of the device is protected with photoresist and adhered to a quartz substrate with paraffin wax. The back InP substrate and InGaAs sacrificial layer are removed sequentially with hydrochloric acid and a mixture of H3PO4 / H2O2. Au is deposited on the back side of the InP back field layer using electron beam evaporation and adhered to a quartz or silicon substrate with an adhesive. The paraffin wax and photoresist on the front side are removed with carbon tetrachloride and acetone, resulting in an Au / InP / In... 1-x Ga x As y P 1-y / InP structure battery devices.
Citation Information
Patent Citations
Photovoltaic cell
CN102227816A
Solar cell with epitaxially grown quantum dot material
CN103003954A